Retorno a las bases de la exclusión: Las diferencias raciales como pretexto - García Martínez, Alfonso; Sánchez Lázaro, Antonia Mª (Nómadas. Critical Journal of Social and Juridical Science, 2013)
The processes of persons' spatial mobility and groups with traditions and different cultures (with the consequent positive and negative contacts with other cultural forms), acquire at present specific characteristics that separate them basically from the occurred in the past. In effect, the configuration of the diverse human societies in national States has carried that the presence of persons proceeding from other States they awards automatically, in the majority of the occasions, a socio-political statute differently, that of foreigners. On the other hand, the consolidation of the historical construction of the idea of 'race' (of direct form or under the coverage of his picture, the 'etnic minority') has created in the bosom of the multicultural societies very deep fractures between(among) groups belonging to such 'etnic minorities' or different 'races' (García and Sáez, 1998); based breaks not only in more or less distorted and stereotyped perceptions, but also in the occupation of differentiated strata of power, even when to some of these groups they is recognized the nationality of the corresponding country.
Keywords: 'race'; 'etnic minority'; science; ordinary knowledge; exclusion; racism; migrations; interculturalism